2021
DOI: 10.3390/en14051401
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Intrusion Mitigation Unit for Interconnected Power Systems in Frequency Regulation to Enhance Cybersecurity

Abstract: Cyberattacks (CAs) on modern interconnected power systems are currently a primary concern. The development of information and communication technology (ICT) has increased the possibility of unauthorized access to power system networks for data manipulation. Unauthorized data manipulation may lead to the partial or complete shutdown of a power network. In this paper, we propose a novel security unit that mitigates intrusion for an interconnected power system and compensates for data manipulation to augment cybe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Fractional order PID controller Improves the performance of the PID controller and protects the frequency, speed regulator and biasing factor from CA. [216,217] BADAL ET AL.…”
Section: Follow Operation Modementioning
confidence: 99%
“…Fractional order PID controller Improves the performance of the PID controller and protects the frequency, speed regulator and biasing factor from CA. [216,217] BADAL ET AL.…”
Section: Follow Operation Modementioning
confidence: 99%
“…Recently, an optimal two-stage Kalman filtering approach has been proposed to handle the template attacks and has been validated on benchmark mulit-area power systems [58]. In [59], the authors suggested installing an automatic intrusion mitigation unit supported with PID controller that can not only protect the LFC operation against the cyber-attack, but also against power system model uncertainties and external noises.…”
Section: False Data Injection Preventionmentioning
confidence: 99%